2011
DOI: 10.1371/journal.pone.0016632
|View full text |Cite
|
Sign up to set email alerts
|

Troublesome Heterotopic Ossification after Central Nervous System Damage: A Survey of 570 Surgeries

Abstract: BackgroundHeterotopic ossification (HO) is a frequent complication after central nervous system (CNS) damage but has seldom been studied. We aimed to investigate features of HO for the first time in a large sample and the rate of early recurrence of HO in terms of the time of surgery.Methodology/Principal FindingsWe retrospectively analyzed data from an anonymous prospective survey of patients undergoing surgery between May 1993 and November 2009 in our institution for troublesome HO related to acquired neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 35 publications
7
90
1
1
Order By: Relevance
“…Therefore, we choose the method of revision surgical resection in our case study. (2,3,13,14) Conclusion HO presents multiple diagnostic and therapeutic challenges. Although clinically significant HO occurs infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we choose the method of revision surgical resection in our case study. (2,3,13,14) Conclusion HO presents multiple diagnostic and therapeutic challenges. Although clinically significant HO occurs infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…After wound closure, postoperative AP and lateral radiographs of the residual limb were obtained as baseline images. The rats were maintained for 24 weeks, and serial orthogonal radiographs of the residual limb were obtained at 10 days and at 4,8,12,16,20, and 24 weeks. Euthanasia was planned for all animals at 24 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Abnormal growth results from a disturbance in regulation of normal skeletogenesis and frequently is encountered in other orthopaedic settings, including THA and elbow fracture [1, 3, 11, 20-22, 24, 25] and traumatic brain injury and spinal cord injury [4,8]. Despite being documented as far back as the Civil War, few comprehensive reports on HO frequency in combat-related injuries exist [7,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is known to occur after blunt trauma elbow and acetabular fractures, burns, traumatic brain injury, and spinal cord injury. Recently, interest in HO has increased as a result of its high prevalence in combat-related extremity injuries and amputations [9,10,14,15,17]. Studies have reported the prevalence of HO to be as high as 65% in combat-related amputations, and HO can result in pain, wound breakdown, difficulty with prosthesis wear, entrapment of neurovascular structures, and limited ROM [2,4,6,16,18,20,22,23,26,29,31,32,35].…”
Section: Introductionmentioning
confidence: 99%